2014
DOI: 10.1177/0961203314547797
|View full text |Cite
|
Sign up to set email alerts
|

Urine β2-microglobulin is associated with clinical disease activity and renal involvement in female patients with systemic lupus erythematosus

Abstract: We demonstrated that urine β2MG levels are associated with renal involvement and overall clinical disease activity in SLE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
(51 reference statements)
0
23
0
Order By: Relevance
“…to define active disease. [28][29][30][31][32][33] Additionally, it is important to point out that the cut-off selection presented by Yee et al 24 underlines the importance of considering the SLEDAI-2K score as a continuous scale, especially in longitudinal studies. Therefore, in this study we also analyzed the relationship of dsDNA positivity by the CIA in relation to the SLEDAI-2K score and found significantly higher scores in the CIA-positive versus the CIA-negative SLE patients (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…to define active disease. [28][29][30][31][32][33] Additionally, it is important to point out that the cut-off selection presented by Yee et al 24 underlines the importance of considering the SLEDAI-2K score as a continuous scale, especially in longitudinal studies. Therefore, in this study we also analyzed the relationship of dsDNA positivity by the CIA in relation to the SLEDAI-2K score and found significantly higher scores in the CIA-positive versus the CIA-negative SLE patients (p < 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the recent animal toxicology data raise important questions about both the specificity of urinary β 2 M for tubular lesions, i.e., this compound appears to detect glomerular injury better than tubular damage, and its overall utility relative to the more easily obtained assay for albuminuria. Interestingly, significant correlations between urinary β 2 M and other indices of renal damage (e.g., protein/Cr ratio) have been reported in IgA nephropathy (163) and systemic lupus erythematosus (164). Both these conditions are characterized by predominantly glomerular lesions.…”
Section: Urinary β2m For the Assessment Of Tubular Functionmentioning
confidence: 99%
“…After therapy, the serum β 2 M level decreased significantly (268). Urinary β 2 M has been shown to correlate with overall and renal disease activity scores and proteinuria (164). Patients with active primary Sjögren’s syndrome, notably those with increased systemic disease activity (302) and history of lymphoma (303, 304), and hemophagocytic lymphohistiocytosis (305) were also found to have elevated urinary β 2 M level.…”
Section: β2m In Non-renal Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteins of low molecular weight, such as α1-microglobulin (α1-MG) (31.8 kD) or β2-microglobulin (β2-MG) (11.8 kD), are excreted in large quantities when proximal tubular cells lose their capacity to reabsorb them; therefore, these proteins reflect intrinsic tubular injury [ 19 ]. Studies have shown that serum and urinary levels of β2-MG were associated with renal involvement in SLE [ 20 , 21 ], as well as urinary albumin (UAL) [ 22 ], IgG, and α1-MG [ 23 ]. Physiologically, α1-MG is involved in the defense against oxidative tissue damage [ 24 ], while β2-MG is a component of the MHC class I [ 25 ].…”
Section: Introductionmentioning
confidence: 99%